2018
DOI: 10.1101/261586
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Whole genome sequencing reveals the emergence of aPseudomonas aeruginosashared strain sub-lineage among patients treated within a single cystic fibrosis centre

Abstract: BackgroundChronic lung infections by Pseudomonas aeruginosa are a significant cause of morbidity and mortality in people with cystic fibrosis (CF). Shared P. aeruginosa strains, that can be transmitted between patients, are of concern and in Australia the AUST-02 shared strain is predominant in individuals attending CF centres in Queensland and Western Australia. M3L7 is a multidrug resistant sub-type of AUST-02 that was recently identified in a Queensland CF centre and was shown to be associated with poorer c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…It has previously hypothesized that virulence factors are selected against in CF infections, and in agreement with this we found that 34 of the 52 highly variable genes were lost as part of a genomic region encoding virulence factors hydrogen cyanide synthase (hcnABC) and type III secreted protein ExoY (exoY). It has also been shown by Wee et al (2018) [31] that selective pressures for losing hcnA, hcnB, hcnC and exoY genes exist, and we notice that Wee et al…”
Section: Convergent Evolution and Adaptive Loss Of Virulencesupporting
confidence: 61%
See 1 more Smart Citation
“…It has previously hypothesized that virulence factors are selected against in CF infections, and in agreement with this we found that 34 of the 52 highly variable genes were lost as part of a genomic region encoding virulence factors hydrogen cyanide synthase (hcnABC) and type III secreted protein ExoY (exoY). It has also been shown by Wee et al (2018) [31] that selective pressures for losing hcnA, hcnB, hcnC and exoY genes exist, and we notice that Wee et al…”
Section: Convergent Evolution and Adaptive Loss Of Virulencesupporting
confidence: 61%
“…Literature search identified that four of the genes (hcnABC and exoY encoding hydrogen cyanide synthase and type III secreted protein, respectively) are known to play a role in virulence and pathogenesis of P. aeruginosa. [30,31]…”
Section: Convergent Evolution Of Locus With Hcnabc and Exoy Genesmentioning
confidence: 99%
“…Chronic infection of CF lungs with highly adapted and antibiotic resistant biofilms of P. aeruginosa is a major cause of lung function decline, which results in a concomitant increase in morbidity and mortality in individuals with CF (3,4,(6)(7)(8)(9)(10)(11). Longitudinal studies of chronic CF infections with P. aeruginosa have revealed that patients become infected at a young age with an environmental or transmissible isolate that evolves and adapts over time to the lung environment (12)(13)(14)(15)(16)(17)(18). Studies on P. aeruginosa populations isolated from individual lungs, have demonstrated divergent evolution, resulting in heterogeneous populations of P. aeruginosa within patients (16,17,19).…”
Section: Introductionmentioning
confidence: 99%